2017
DOI: 10.4314/jfas.v9i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical behaviour of a roller compacted concrete reinforced with polypropylene fiber

Abstract: In order to study the behaviour of a roller compacted concrete (RCC) reinforced with polypropylene fiber, six types of RCC were made with different content of fibers (0, 0.5, 1, 1.5, 2 and 2.5 Kg/m 3 ). The physical parameters are the density, the workability, the shrinkage and the water absorption. For the mechanical parameters; the performances such as the compressive strength and the tensile strength (3 point bending and splitting) has been studied.The results show that the RCC reinforced with fibers presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…Natural pozzolan inclusion to RCC mixtures resulted in a decrease of Ve-Be time and workability property (Ghahari et al, 2017). Similarly with the addition of polypropylene fibre, workability decreases as reported in a study (Benouadah et al, 2017). This can be attributed to the high water absorption properties of natural pozzolans.…”
Section: Workability and Setting Timessupporting
confidence: 67%
See 2 more Smart Citations
“…Natural pozzolan inclusion to RCC mixtures resulted in a decrease of Ve-Be time and workability property (Ghahari et al, 2017). Similarly with the addition of polypropylene fibre, workability decreases as reported in a study (Benouadah et al, 2017). This can be attributed to the high water absorption properties of natural pozzolans.…”
Section: Workability and Setting Timessupporting
confidence: 67%
“…It was observed that steel efficiency in RCC is significantly higher than in conventional concrete (Karadelis and Lin, 2015). Polypropylene fibre has also similar increasing effect on RCC (Benouadah et al, 2017).…”
Section: Evaluation Of Compressive Strengthmentioning
confidence: 84%
See 1 more Smart Citation
“…Benouadah, et al [12], studied the effect of polypropylene fiber (PPF) on the drying shrinkage of RCC pavement. They prepared six mixes by adding 0, 0.5, 1, 1.5, 2 and 2.5 kg/m 3 of PPF.…”
Section: Introductionmentioning
confidence: 99%
“…But unlike conventional concrete, it is a drier mix-stiff enough to be compacted by vibratory rollers. Therefore, the fundamental characteristic of RCCP is its dry appearance, which requires the application of compaction efforts to consolidate the mix [3]. Little information is available on the performance of rubberized RCCP, because the majority of researches are conducted on conventional rubberized concrete and as such very little have been reported on RCCP mixes [6,[9][10][11]16].…”
Section: Introductionmentioning
confidence: 99%